Block‐windowed burst OFDM: a high‐efficiency multicarrier technique. Issue 23 (1st November 2014) - Nunes, J.; Bento, P.; Gomes, M.; Dinis, R.; Silva, V.
Abstract : A block‐windowed burst orthogonal frequency division multiplexing (OFDM) technique which is a multicarrier technique with power spectral density similar to the filtered OFDM approach, since it also employs smoother, non‐rectangular windows, is presented. However, it does not need a cyclic prefix, which means the overall power and spectral efficiencies are higher. An appropriate receiver for typical time‐dispersive channels, allowing 2 dB of gain relatively conventional OFDM schemes is also presented.